PENGEMBANGAN APLIKASI PERPUSTAKAAN MOBILE DI LINGKUNGAN UNIVERSITAS LANCANG KUNING - Hidayat, Rahmat; Darmayunata, Yufi (Universitas Muhammadiyah Riau, 2026)
Libraries play an essential role in supporting academic activities in higher education. However, the limitations of web-based systems have hindered students of Universitas Lancang Kuning from optimally accessing digital collections via mobile devices. This study aims to develop a mobile library application for Android integrated with SLiMS as a data management API. The research employed the prototype method, involving requirements analysis, system design using UML, interface design, prototype development, and user feedback testing. The results show that the application runs properly on the Android platform, integrates with SLiMS for data communication, and enables users to access book collections and read digital books directly. The application performance depends on internet stability, but its features support efficiency and accessibility of library services. Therefore, this mobile application is expected to be a solution for the digitalization of library services at Universitas Lancang Kuning.